Quercetin 3,5,7,3′,4′-pentamethyl ether from Kaempferia parviflora directly and effectively activates human SIRT1 - Mimin Zhang (Communications Biology, 2021)
A compound from Thai black ginger, KPMF-8, was previously found to dramatically promote activation of SIRT1 towards a peptide substrate. Zhang et al. now show that KPMF-8 can be taken up by cells through culture media, directly interacts with SIRT1, and promotes its deacetylation activity toward native substrate more effectively than resveratrol.